THE EFFECTIVENESS OF USING THE DORATOON ANIMATION MAKER LEARNING MEDIA IN SEMANTIC COURSES IN INDONESIAN LANGUAGE AND LITERATURE EDUCATION STUDENTS FBS UNIMED - Azhar Umar; Inayah Hanum; Trisnawati Hutagalung (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
This study discusses the effectiveness of learning Semantics courses using learning media based on Doratoon Animation Maker for students in the Indonesian Language and Literature Education Study Program. The purpose of this study was to see the effectiveness of Doratoon Animation Maker's teaching materials in the utilization of the learning process in Semantics courses. This population is all fourth semester students of the 2022/2023 academic year of the Indonesian Language and Literature Education Study Program. The sample of this research is the fourth semester students of regular class A in the 2022/2023 academic year of the Indonesian language and literature study program. The research instruments used were observation, questionnaires, and special tests. This research uses the Research and Development method. The results of this study, namely before using Doratoon Animation Maker learning media in Semantic learning get an average score of 67, 3 and after using Doratoon Animation Maker based learning media get an average of 85, 5.